1992
DOI: 10.1254/jjp.59.387
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the Association of Brotizolam, a Thieno-Triazolo Diazepine Derivative, with the Benzodiazepine Receptor: A Selective and High Affinity Ligand of the Central Type I Benzodiazepine Receptor.

Abstract: ABSTRACT-Characteristics of the association of brotizolam, a thieno-triazolo diazepine derivative, to central benzodiazepine receptors were examined. Brotizolam significantly displaced the [3H]flunitraz epam and [3H]/3-carboline carboxylate ethylester bindings to crude synaptic membrane from the rat brain. This agent had the highest affinity for benzodiazepine receptors in the cerebellum, and it was found to be 2.1 times that in the spinal cord. Furthermore, a low concentration of brotizolam poten tiated the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This lack of residual effects of hypnotic agents 9.75 h after dosing suggested that the dose of the hypnotic agents was within a reasonable range. Consistently, it has been reported that, after single and repeated doses of suvorexant, its residual effects on driving performance in the morning were negligible (35,36). As this was an initial study with forced awakening under the maximal influence of suvorexant, a new class of hypnotics, we enrolled relatively young, healthy individuals in consideration of their safety.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This lack of residual effects of hypnotic agents 9.75 h after dosing suggested that the dose of the hypnotic agents was within a reasonable range. Consistently, it has been reported that, after single and repeated doses of suvorexant, its residual effects on driving performance in the morning were negligible (35,36). As this was an initial study with forced awakening under the maximal influence of suvorexant, a new class of hypnotics, we enrolled relatively young, healthy individuals in consideration of their safety.…”
Section: Discussionmentioning
confidence: 71%
“…The differential effects of suvorexant and brotizolam are likely related to the fundamental differences in their mechanisms of action. Balance is coordinated by the cerebellum (35), in which benzodiazepine receptors are abundantly expressed (36). In contrast, the cerebellum is free from the direct effects of orexin; orexin-producing neurons essentially send no projections to the cerebellum (37), where very little expression of orexin receptors has been documented (38).…”
Section: Discussionmentioning
confidence: 99%
“…In our study, it was ascertained that zolpidem (data not shown) and ~-CCE, BZ,-selective ligands (6,10), had about five times higher affinities for the BZ receptors in the cerebellum than those in the spinal cord. The physiological roles of the BZ, and BZ2 receptors in brain function are not yet clarified, but the sedative and ataxic effects by BZs have been proposed to be due to the over activation of the BZ, and BZ2 receptors, respectively (16)(17)(18). Findings that abecarnil had no ataxic effects may be partly due to its lower affinity for spinal cord BZ2 receptors, but it does not explain the antagonism of diazepam-induced ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that there are two dis tinct central types of BDZ-binding site (BDZ| and BDZ?) and one peripheral type (BDZ3) [17,18].BDZ| is related to hypnotic, anticon vulsant, and anxiolytic effects, while BDZ2 is related to the muscle-relaxant effect [17][18][19], Furthermore, BDZr binding sites predomi nate in the cerebellum, while BDZ2 is en riched in the spinal cord; the limbic area con tains both central types [17][18][19]. In prelimina ry observations, Ro 41-3696, like zopiclone [18,20], exhibited higher affinity binding in the rat cerebellum than in the limbic area.…”
Section: Discussionmentioning
confidence: 99%